All Days 2001
DOI: 10.2118/68854-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Test of a Novel Low Viscosity Fracturing Fluid in the Lost Hills Field, California

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe Monterey formation, Belridge Diatomite is a high porosity (45%) low permeability (0.5 -7 md), low Young's modulus (~100,000 psi) oil reservoir with few stress barriers for fracture containment. Due to the low permeability it is desirable to optimize the fracture length per pound of proppant placed. Conventional cross-linked fluids are not well suited for this purpose as they create excessive width -reducing the effective fracture length generated for a gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Systems with such a viscosity can hold the proppant volume in the well and transport it to the resulting fracture, thereby ensuring high efficiency of the whole operation. Rotational viscometry is a widely used method for determining the effective viscosity of fracturing fluids [49][50][51][52][53]. However, this type of measurement does not fully describe the structural and mechanical properties of liquids, which leads to a reduced spread of systems based on VES and synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Systems with such a viscosity can hold the proppant volume in the well and transport it to the resulting fracture, thereby ensuring high efficiency of the whole operation. Rotational viscometry is a widely used method for determining the effective viscosity of fracturing fluids [49][50][51][52][53]. However, this type of measurement does not fully describe the structural and mechanical properties of liquids, which leads to a reduced spread of systems based on VES and synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies had reported the rheological properties of fiberassisted fracturing fluid and the effects of fiber on the rheological characterization for fracturing fluids that may not be uniform. Vasudevan et al (2001) first reported that the addition of fiber increased the apparent viscosity of linear guar fracturing fluid and led to a three-time increment. However, it was still much lower than the borate cross-linked fracturing fluid under the same condition.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of fibers on bridging have been studied in [22,23] based on the partitioning of energy approach following Bagnold's theory. Flow energy imparted to the moving slurry is partitioned into useful shear work, kinetic energy of particles, and a portion lost in dissipative solid-body interactions.…”
Section: Introductionmentioning
confidence: 99%
“…More sophisticated criteria take into account experimental observations [15], which demonstrate that the critical width is also dependent upon the concentration of proppant upstream of the bridging point. Although the original criterion of [15] was developed for modeling bridging at perforations, there was a modified version of bridging criterion in a fracture, which demonstrates [18,1] w * = min b, 1 + C p 0.17 The effects of fibers on bridging have been studied in [22,23] based on the partitioning of energy approach following Bagnold's theory. Flow energy imparted to the moving slurry is partitioned into useful shear work, kinetic energy of particles, and a portion lost in dissipative solid-body interactions.…”
Section: Introductionmentioning
confidence: 99%